Perancangan dan Implementasi Programmable Function Generator menggunakan H-Bridge L298N untuk Rangkaian Wireless Power Transfer - Arya Rizky Imansyah Harahap; Sabriansyah Rizqika Akbar; Eko Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
One of the factors that affect the level of power transfer efficiency in Wireless Power Transfer (WPT) technology is the frequency of the voltage used on the coil. Not just any voltage frequency can be used, but there are frequency peaks that can maximize the efficiency of WPT power transmission. To overcome this problem, this study designed a programmable function generator that can produce AC waves in the form of square waves which can be programmed using a microcontroller in the output frequency range of 100 Hz to 25 kHz to be tested in the Wireless Power Transfer circuit. This system utilizes the Arduino UNO PWM phase change period with a 50% duty cycle so that a square wave output with a certain frequency is produced on the H-Bridge L298N. This method obtains an accuracy of the output square wave frequency of 99,46% with the highest error value of 1,992%. Implementation of the system in the WPT circuit by analyzing frequency changes in the range 1 kHz to 25 kHz and a distance of 1 cm to 3 cm, the maximum received power value is obtained in the receiver circuit of 79,72 mW at a distance of 1 cm; 73,68 mW at a distance 2 cm; and 53,24 mW at a distance of 3 cm. The maximum power transmission efficiency values obtained in the test were 7,76% at a distance of 1 cm; 7,558% at a distance of 2 cm; and 3,71% at a distance of 3 cm.